RANLP 2017 - Recent Advances in Natural Language Processing Meet Deep Learning 2017
DOI: 10.26615/978-954-452-049-6_004
|View full text |Cite
|
Sign up to set email alerts
|

Persian–Spanish Low-Resource Statistical Machine Translation Through English as Pivot Language

Abstract: This paper is an attempt to exclusively focus on investigating the pivot language technique in which a bridging language is utilized to increase the quality of the Persian-Spanish low-resource Statistical Machine Translation (SMT). In this case, English is used as the bridging language, and the Persian-English SMT is combined with the English-Spanish one, where the relatively large corpora of each may be used in support of the Persian-Spanish pairing. Our results indicate that the pivot language technique outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Phrase table combination could also be used in pivot approaches to overcome the data scarcity between src-trg language pairs [1][2][3][4]6,13,14]. The phrase table combination outperformed direct translation or other pivot approaches, namely, sentence translation and triangulation.…”
Section: Related Work 21 Phrase Table Combinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Phrase table combination could also be used in pivot approaches to overcome the data scarcity between src-trg language pairs [1][2][3][4]6,13,14]. The phrase table combination outperformed direct translation or other pivot approaches, namely, sentence translation and triangulation.…”
Section: Related Work 21 Phrase Table Combinationmentioning
confidence: 99%
“…The phrase table combination outperformed direct translation or other pivot approaches, namely, sentence translation and triangulation. We identified that the phrase table combination in the pivot approaches uses the same symmetrization of word alignment, i.e., gdfand [1][2][3][4]6,13,14]. This is because the gdfand is a standard symmetrization of word alignment in statistical machine translation (SMT) [7].…”
Section: Related Work 21 Phrase Table Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal and informal translations address several different characteristics. Inflection, declination and grammatical gender are important features of Spanish language [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, English as lingua franca has more datasets compared to other languages. Thus, pivot researchers commonly use English as a bridge between source to target (Paul et al, 2013;El Kholy et al, 2013;Ahmadnia et al, 2017;Dabre et al, 2015;Trieu, 2017). However, Paul et al, (2013) and Dabre et al, (2015) have shown that using non-English as pivot language could be a better option to improve the translation results for particular language pair.…”
Section: Introductionmentioning
confidence: 99%